Characteristic of slow growth in cell culture of adenovirus type 54 causing nationwide outbreak epidemic keratoconjunctivitis in Japan - Tsukahara-Kawamura, Tomoko; Hanaoka, Nozomu; Konagaya, Masami; Uchio, Eiichi; Fujimoto, Tsuguto (Japanese journal of ophthalmology, 2020)
Purpose To characterize the virological features of adenovirus type 54 (Ad54) causing nationwide outbreak of severe epidemic keratoconjunctivitis (EKC) in Japan, we comparatively analysed the viral propagation phenotype of Ad54 and other Ads: type 37 (Ad37), 64 (Ad64), and 5 (Ad5), in A549 cells quantitatively. Study design Laboratory investigation. Methods We compared the growth rate of Ads using copy numbers and cytopathic effect observation during propagation in A549 cell lines. Expressions of mRNA of E1 gene were also calculated and compared. Phylogenetic analysis of the region, including putative promoter of E1 gene and E1 open reading frame (ORF), were performed. Results Increases in viral loads, growth rate, and viral propagation were slower for Ad54 than for other Ads. The expression level of the E1 gene per infected cell was lower for Ad54 than for other Ad types on post-infection day 1. Phylogenetic analysis of the E1 gene putative promoter and ORF revealed Ad54 was the closest to Ad type 8. Conclusion The propagation of Ad54 in A549 is slow compared with Ad37, Ad64 and Ad5. This slow propagation could have been caused by slow genomic replication resulting from delayed viral entry or E1 transcription initiation. The EKC caused by Ad54 needs more attention because the slow propagation of Ad54 may contribute to prolonged disease duration.